Penerapan Prinsip Maqāṣid Al-Sharī'ah Dalam Rancang Bangun Sistem Ekonomi Islam Di Indonesia : Rancang Bangun Ekonomi Islam - Gusnawati Nurbaba; Damirah (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2025)
The integration of Maqāṣid al-Sharī‘ah principles into the design of the Islamic economic system is essential to achieve social justice and collective prosperity in Indonesia. The Islamic economy must not be limited to formal sharia compliance but should aim toward maqāṣid compliance, the realization of the five objectives of Sharia: the preservation of faith (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl). This study explores the integration between the conceptual framework of Islamic economics based on the principles of tawḥīd (monotheism), justice, prophethood, governance, and accountability in the hereafter and the practical application of maqāṣid in the national economic context. Using a descriptive qualitative method, this paper analyzes how maqāṣid serves as both a normative and operational instrument in formulating Islamic economic policies, ranging from microfinance, zakat and waqf systems, to the emerging Islamic digital economy. Findings show that a comprehensive application of maqāṣid can strengthen Indonesia’s Islamic economic architecture, promoting equity, sustainability, and human-centered development.Keywords: Maqāṣid al-Sharī‘ah, Islamic Economic Design, Welfare, Social Justice, Indonesia.